Regenerated crude fiber modification method and preparation method of fiber-reinforced ultra-high performance concrete
By modifying the regenerated crude fibers with graphene oxide surface, the problem of insufficient strength in the interface transition zone between fiber and matrix in ultra-high performance concrete is solved, the compressive and tensile properties are improved, and the high value of fiber-reinforced composite materials is promoted. Recycling and sustainable development.
Patent Information
- Application Number
- CN202411177187.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-07
AI Technical Summary
Ultra-high performance concrete has high production costs and a large carbon footprint, which is mainly due to the introduction of expensive steel fibers, and the incorporation of crude fibers will lead to a reduction in compressive strength, which requires improving the interfacial transition zone strength between the fiber and the concrete matrix.
The regenerated crude fibers are modified by using graphene oxide. The regenerated crude fibers are dissolved in water for ultrasonic dispersion, and the waste of fiber reinforced composites is cut into regenerated crude fibers. After heating and stirring in the graphene oxide solution Dry to form modified fibers, increasing the interface bonding force between the fiber and the concrete matrix.
The compressive and tensile properties of crude fibers in ultra-high performance concrete are improved, the utilization efficiency of fiber-reinforced composite materials is optimized, the high-value recycling of waste is promoted, and the production cost and carbon footprint are reduced.
Smart Images

Figure CN119263678A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optimized utilization of recycled composite materials, and in particular relates to a method for modifying recycled crude fibers and a method for preparing fiber-reinforced ultra-high performance concrete. Background Art
[0002] Ultra-high performance concrete (UHPC) is increasingly being used due to its excellent mechanical properties and superior durability. Its compressive strength is typically higher than 120 MPa. In addition, the chloride ion penetration resistance of UHPC is 50 times that of ordinary concrete. Therefore, UHPC has been widely used in the construction of new structures such as bridges, and buildings. However, the production cost of UHPC is as high as 10 to 20 times that of ordinary concrete, limiting its wider application. The high production cost is mainly attributed to the introduction of expensive steel fibers, which account for about 50% of the total production cost. In addition, the production of blended steel fibers significantly increases the carbon footprint of producing UHPC, thereby hindering its wider application.
[0003] Replacing steel fibers in UHPC with coarse-fibered fiber-reinforced composites (i.e., recycled coarse fibers) can result in an inexpensive UHPC. When coarse fibers are incorporated, the flexural strength and toughness of the UHPC are increased by orders of magnitude, respectively. In addition, with the optimization of the structure (i.e., the application of layered beam structures), the utilization efficiency of coarse fibers will be improved. However, similar to other non-metallic fibers, the incorporation of coarse fibers will lead to a decrease in the compressive strength of UHPC. This decrease can be attributed to the hydrophobicity of the coarse fiber surface, which in turn leads to a weak interface transition zone between the coarse fibers and the concrete matrix. Therefore, the interface needs to be strengthened to mitigate the negative impact of the incorporation of coarse fibers on the compressive strength of UHPC.
[0004] Graphene oxide (GO) is characterized by the presence of carboxyl (-COOH), hydroxyl (-OH) and other oxygen-containing functional groups, showing excellent hydrophilicity and having broad application prospects. In addition, GO's unique two-dimensional sheet-like nanostructure and hydrophilicity enable it to modify the interface, especially in the interface transition zone between reinforcing fibers and cement paste. Studies have confirmed that the modification of the surface coating of various fibers (such as polyethylene fibers, steel fibers and carbon nanofibers) by graphene oxide helps to improve their interfacial bonding with cement-based materials. The basic principle is that graphene oxide is adsorbed on the original fiber, acting as a medium to adsorb free calcium ions in cement, thereby accelerating the release of calcium ions in cement, promoting cement hydration closer to the fiber surface, and promoting the bonding of the original fiber with the matrix of the water-containing cement-based material.
[0005] In summary, the development of a surface coating modification technology for the graphene oxide modified method for recycled crude fiber can more specifically improve the surface hydrophobicity of the crude fiber, help improve the strength of the interface transition zone between the crude fiber and the ultra-high performance concrete matrix, and then optimize the utilization of crude fiber in ultra-high performance concrete, and promote the high-value recycling of fiber-reinforced composite materials (especially their waste). Summary of the invention
[0006] The purpose of the present invention is to provide a method for modifying recycled crude fibers, which provides a technically feasible and easy-to-operate approach to optimize the utilization of recycled crude fibers in ultra-high performance concrete, and is of great significance for promoting the high-value recycling of fiber-reinforced composite materials (especially their waste).
[0007] The present invention is achieved by a method for modifying regenerated crude fiber, which comprises at least the following steps:
[0008] Dissolving solid graphene oxide in water and performing ultrasonic dispersion to obtain a uniformly dispersed graphene oxide solution;
[0009] Processing fiber-reinforced composite waste into recycled raw fibers by cutting;
[0010] treating the regenerated crude fiber with a surface crosslinking agent and drying the regenerated crude fiber;
[0011] The regenerated crude fiber is immersed in a graphene oxide solution, subjected to a temperature treatment, accompanied by stirring, and then dried to obtain a modified crude fiber.
[0012] The present invention adopts clean tap water or deionized water as a solvent to prepare a graphene oxide solution.
[0013] The present invention presets a suitable coarse fiber aspect ratio and prepares the fiber-reinforced composite material into coarse fibers through cutting.
[0014] The present invention uses clean tap water or deionized water to clean the surface of the crude fiber, treats the surface of the crude fiber with a crosslinking agent, and dries the crude fiber.
[0015] The present invention immerses the crude fiber in a constant temperature graphene oxide solution, gradually increases the temperature of the solution, and stirs the crude fiber. The graphene oxide gradually shrinks as the temperature increases, while the volume of the crude fiber remains substantially unchanged, so that the graphene oxide is better attached to the surface of the crude fiber. The crude fiber is then dried to obtain a modified fiber.
[0016] The present invention uses a cutting machine to process the fiber-reinforced composite material into coarse fibers with a width of about 3 mm and an aspect ratio of about 30-120.
[0017] Furthermore, the fiber-reinforced composite material used as a raw material for fiber production may be a material that has been used for a certain number of years or has been scrapped, or may even be a newly manufactured fiber-reinforced composite material.
[0018] Furthermore, the crosslinking agent is preferably one or more of an olefin crosslinking agent, an organosilicon crosslinking agent and an epichlorohydrin resin crosslinking agent.
[0019] After the regenerated crude fiber is immersed in the graphene oxide solution, the solution is placed in a water bath heating environment, and the solution temperature is increased from room temperature to 60 degrees within 30 minutes, accompanied by stirring the crude fiber.
[0020] Furthermore, the stirring step of the present invention can be performed manually by stirring the coarse fiber and the graphene oxide solution without damaging the fiber, or can be performed automatically by a machine.
[0021] Another object of the present invention is to provide a method for preparing fiber-reinforced ultra-high performance concrete, so as to provide reinforced and toughened ultra-high performance concrete containing the modified recycled coarse fiber.
[0022] Specifically, a method for preparing fiber-reinforced ultra-high performance concrete comprises preparing modified crude fibers according to the above-mentioned recycled crude fiber modification method, and adding the modified fibers to an ultra-high performance concrete matrix for reinforcement to obtain modified crude fiber-reinforced ultra-high performance concrete.
[0023] In the present invention, among the raw materials used for preparing fiber-reinforced ultra-high performance concrete, the mass proportion of cement in the system is 1, and the proportions of the remaining components are respectively: 0.5-0.14 of modified crude fiber, 0.25 of silica fume, 0.25 of limestone powder, 0.7-1.1 of fine aggregate, 0-0.4 of coarse aggregate, 0.23 of water and 0.02-0.03 of water reducer.
[0024] The cement is cement with a compressive strength grade of 52.5 or above.
[0025] Another object of the present invention is to provide a fiber-reinforced ultra-high performance concrete.
[0026] The fiber-reinforced reinforced concrete comprises modified coarse fibers, the surface of the modified coarse fibers is coated with a certain amount of graphene oxide coating, and the aspect ratio of the modified coarse fibers is 30-120.
[0027] Furthermore, by mass, the mass proportion of cement in the system is set to 1, and the remaining components and their mass proportions are: crude fiber 0.5-0.14, silica fume 0.25, limestone powder 0.25, fine aggregate 0.7-1.1, coarse aggregate 0-0.4, water 0.23 and water reducer 0.02-0.03.
[0028] Furthermore, the cement used in the ultra-high performance concrete is cement with a compressive strength grade of 52.5 or above.
[0029] Furthermore, the graphene oxide attached to the surface of the modified crude fiber in the ultra-high performance concrete can adsorb free calcium ions after cement hydration near the interface, thereby accelerating the release of calcium ions in the cement and improving the strength of the interface area.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The regenerated crude fiber modification method provided by the present invention can make full use of the advantages of graphene oxide nanomaterials, has the characteristics of high technical feasibility and simple process, and is particularly suitable for improving the interface transition zone between the regenerated crude fiber and the ultra-high performance concrete matrix. The present invention provides a technically feasible and easy-to-operate approach to optimize the use of crude fibers in ultra-high performance concrete, which is of great significance for promoting the high-value recycling of fiber-reinforced composite waste. Among them, except for graphene oxide and cross-linking agent, no other additional substances are introduced into the surface of the crude fiber, which is more conducive to the fiber maintaining its material stability.
[0032] In addition, adding the modified crude fiber obtained by surface modification as a reinforcing phase into ultra-high performance concrete can further improve the compressive and tensile properties of the original crude fiber reinforced ultra-high performance concrete. It can be seen that the present invention is of great significance for the further promotion and application of recycled composite materials and the creation of sustainable ultra-high performance cement-based materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a flow chart of surface modification of waste coarse fiber reinforced composite materials provided by an embodiment of the present invention;
[0034] Figure 2 is a SEM image of the surface of the crude fiber before and after modification provided by the embodiment of the present invention;
[0035] Figure 3 It is a schematic diagram of the transition zone between the coarse fiber and the concrete matrix before and after modification provided by an embodiment of the present invention.
[0036] Figure 4 is a compressive strength diagram of each group of cubic specimens provided by an embodiment of the present invention;
[0037] Figure 5 The force-mid-span displacement curves of each group of beam specimens provided in the embodiment of the present invention are
[0038] Figure 6 It is a single coarse fiber pulling force-displacement diagram provided by an embodiment of the present invention. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0040] See also Figure 1 , showing the regenerated crude fiber modification method provided in this embodiment, the material used in the modification method is graphene oxide, and the modification of the modification object (i.e., crude fiber) includes the following steps:
[0041] S1. Steps for obtaining modified solution:
[0042] The graphene oxide solution required for modification can be obtained in two ways: one is to dissolve a certain amount of graphene oxide powder material in tap water or deionized water, and combine it with 20 minutes of ultrasonic dispersion to evenly disperse the particles in the solution; the other is to directly purchase industrially produced graphene oxide dispersion. And add alkaline buffer (such as sodium bicarbonate) to adjust the pH value of the solution to 5. Before the modification begins, the solution is sealed and stored.
[0043] S2, crude fiber preparation steps:
[0044] Obtain a certain mass of fiber-reinforced composite materials on site, and use appropriate mechanical cutting methods to obtain coarse fibers with a width of about 3 mm and an aspect ratio of about 30-120 from waste of different sizes. Make statistics on the actual size of the fibers and classify the coarse fibers of different sizes.
[0045] S3, crude fiber cross-linking agent treatment steps:
[0046] Place the classified crude fibers on a sieve of appropriate size, rinse them with running tap water or deionized water, and manually turn them over to remove the powder attached to the fiber surface during the cutting process. The cleaning time can be adjusted according to the turbidity of the running water, generally not more than 20 minutes. Then, place the cleaned crude fibers in the crosslinker solution, stir for 30 minutes, and then place them in a drying box for drying at a temperature not exceeding 70 degrees.
[0047] S4, crude fiber modification steps:
[0048] The cleaned crude fiber is immersed in a constant temperature graphene oxide solution, and the solution temperature is gradually increased so that the graphene oxide can be evenly and stably attached to the crude fiber. During the immersion process, manual or mechanical stirring is performed without damaging the crude fiber. The modified crude fiber is then taken out and placed in an oven at a temperature not higher than 70 degrees for drying to obtain the modified crude fiber.
[0049] In summary, the fiber-reinforced composite material is processed into coarse fibers by cutting, then the coarse fibers are treated with a surface crosslinking agent and dried, and finally the coarse fibers are immersed in a graphene oxide solution, the solution is placed in a water bath heating environment, the solution temperature is increased from room temperature to 60 degrees within 30 minutes, and the coarse fibers are stirred, and then dried to obtain modified coarse fibers.
[0050] In order to utilize the modified crude fibers, this embodiment further provides a fiber-reinforced ultra-high performance concrete, which includes a plurality of modified crude fibers. The crude fibers are composed of a resin matrix and continuous fibers embedded in the resin matrix. The aspect ratio of the crude fibers is 30-120.
[0051] This embodiment does not limit the type of continuous fiber and the type of resin matrix, that is, the continuous fiber can be glass fiber, carbon fiber or other fiber, and the resin matrix can be thermosetting resin or thermoplastic resin. In addition, the fiber-reinforced composite material used as a raw material for fiber production can be a material that has been used for a certain number of years or has been scrapped, or can even be a newly made fiber-reinforced composite material.
[0052] Specifically, the components of the ultra-high performance concrete matrix can be appropriately formulated according to specific needs. In order to fully illustrate the present invention, this embodiment lists the following matrix components, by mass, the mass proportion of cement in the system is set to 1, and the remaining components and their mass proportions are: crude fiber 0.5-0.14, silica fume 0.25, limestone powder 0.25, fine aggregate 0.7-1.1, coarse aggregate 0-0.4, water 0.23 and water reducer 0.02-0.03.
[0053] Preferably, the cement is ordinary or early-strength silicate cement with a compressive grade of 52.5 or above, the fine aggregate is river sand, sea sand, artificial sand and other construction sand, the silicon content of silica fume should be greater than 92%, and the particle size of coarse aggregate should not be greater than 9 mm.
[0054] In addition, the protection scope of this embodiment may also include various prefabricated components prepared using the above-mentioned reinforced ultra-high performance concrete and various building components cast at the construction site.
[0055] The regenerated crude fiber modification method of the present invention can make full use of the advantages of graphene oxide nanomaterials, has the characteristics of high technical feasibility and simple process, and is particularly suitable for improving the interface transition zone between crude fiber and ultra-high performance concrete matrix. The present invention provides a technically feasible and easy-to-operate approach to optimize the utilization of crude fiber in ultra-high performance concrete, which is of great significance for promoting the high-value recovery of fiber-reinforced composite materials (especially their waste). Among them, except for graphene oxide, no other additional substances are introduced into the surface of the crude fiber, which is more conducive to the crude fiber to maintain its material stability.
[0056] In addition, adding the surface-modified macrofiber as a reinforcing phase into ultra-high performance concrete can further improve the compressive and tensile properties of the original macrofiber-reinforced ultra-high performance concrete. It can be seen that the present invention is of great significance for further promoting the application of recycled composite materials and creating sustainable ultra-high performance cement-based materials.
[0057] In order to further embody the inventive concept and technical effect of the present invention, the present invention is described in detail below in conjunction with embodiments:
[0058] First, a discarded wind turbine blade (a kind of fiber-reinforced composite waste) was mechanically cut into coarse fibers with a length of 30 mm, a width of 3 mm and a thickness of 0.8 mm. The surface of the coarse fibers was modified using the subsequent steps of this embodiment: (1) After the surface of the coarse fibers was washed with tap water, they were placed in a silane coupling agent KH550 (the coupling agent content was 0.5% by mass) and stirred for 30 minutes, and then dried; (2) The coarse fibers were immersed in a 1 mg / ml graphene oxide solution with the temperature gradually increased from 0 degrees to 60 degrees, stirred for one hour and then dried. Figure 2 It was observed that, in comparison, the modified coarse fibers had an additional graphene oxide covering layer on their surface. Figure 3 The schematic diagram in the middle shows the change mechanism of the transition zone between the crude fiber and the ultra-high performance concrete matrix before and after modification. Graphene oxide can adsorb free calcium ions in cement, thereby accelerating the release of calcium ions in cement and promoting cement hydration on the fiber surface, which in turn helps to reduce the transition zone (i.e., strengthen the transition zone).
[0059] The modified crude fiber prepared above is added to the ultra-high performance concrete matrix according to different contents, which can enhance the compressive strength, flexural strength and toughness of the ultra-high performance concrete containing the same amount of original crude fiber to varying degrees. In order to better compare and study the influence of the modified crude fiber, two kinds of concrete mix ratios are set. Except for the different types of crude fiber, the contents of other components per unit volume remain unchanged. The specific mix ratio information is shown in Table 1, where the types of crude fiber in Group U1 and Group U2 are original crude fiber and modified crude fiber in this embodiment, respectively.
[0060] Table 1: Concrete mix ratio (kg / m3)
[0061]
[0062] Three cube specimens with a side length of 50 mm and three small beam specimens (sizes of 550 mm, 150 mm and 150 mm in length, width and height, respectively) were prepared for each group of ultra-high performance concrete to test their compressive strength and flexural strength respectively; and the change in the bonding force between the macrofiber and the matrix before and after modification was characterized by a single macrofiber pull-out test. The compressive test results show that compared with the control group, the addition of modified macrofiber can further improve the compressive strength of macrofiber-reinforced ultra-high performance concrete; the average 7-day and 28-day compressive strengths of the control group were 94.1MPa and 112.9MPa, respectively, and the average 7-day and 28-day compressive strengths of the modified macrofiber group were 98.6MPa and 120.3MPa, respectively. Figure 5 The force-mid-span displacement curves of each group of small beam specimens are shown, indicating that after the surface modification of the coarse fiber is added to the ultra-high performance concrete, the bending strength and toughness can be further improved. Specifically, the flexural strength is increased from 7.1MPa in the control group to 9.4MPa in the modified coarse fiber group; the toughness is increased from 93.4J / m2 in the control group to 111.8J / m2 in the modified coarse fiber group. Among them, toughness can be quantified as the area under the displacement of the beam specimen force-mid-span displacement curve from 0 to 1 / 150 of the beam span. It is obtained by pulling out a single coarse fiber specimen. Figure 6 The pulling force-displacement curves of each group of specimens shown in the figure indicate that the surface modification of the coarse fiber can effectively improve the interfacial bonding strength between the coarse fiber and the matrix. Specifically, the average maximum pulling force is increased from 0.9 kN in the control group to 1.3 kN in the modified coarse fiber group.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements based on the spirit and principles contained in the present invention should be included in the protection scope of the present invention.
Claims
1. A method for modifying regenerated crude fiber, characterized in that: At least the following steps are included: Dissolving solid graphene oxide in water and performing ultrasonic dispersion to obtain a graphene oxide solution; Processing fiber-reinforced composite materials into recycled raw fibers by cutting; treating the regenerated crude fiber with a surface crosslinking agent and drying the regenerated crude fiber; The regenerated crude fiber is immersed in the graphene oxide solution, heated and stirred, and then dried to obtain modified crude fiber.
2. The method for modifying regenerated crude fiber according to claim 1, characterized in that: The fiber-reinforced composite material is processed into coarse fibers with a width of 3 mm and an aspect ratio of 30-120 by a cutting machine.
3. The method for modifying regenerated crude fiber according to claim 2, characterized in that: The resin matrix of the fiber-reinforced composite material is a thermosetting or thermoplastic resin, and the fiber-reinforced composite material is a newly made fiber-reinforced composite material, a used fiber-reinforced composite material or a waste material.
4. The method for modifying regenerated crude fiber according to claim 1, characterized in that: The crosslinking agent is one or more of an olefin crosslinking agent, an organosilicon crosslinking agent and an epichlorohydrin resin crosslinking agent.
5. The method for modifying regenerated crude fiber according to claim 1, characterized in that: After the regenerated coarse fiber is immersed in the graphene oxide solution, it is subjected to a temperature increase treatment within 30 minutes, accompanied by stirring the coarse fiber.
6. A method for preparing fiber-reinforced ultra-high performance concrete, characterized in that: The modified crude fiber prepared by the regenerated crude fiber modification method according to claims 1 to 5 is added to an ultra-high performance concrete matrix to obtain modified crude fiber reinforced ultra-high performance concrete.
7. The method for preparing fiber-reinforced ultra-high performance concrete according to claim 6, characterized in that: Calculated by mass, with the mass proportion of cement in the system being 1, the other components and their mass proportions are: modified crude fiber 0.5-0.14, silica fume 0.25, limestone powder 0.25, fine aggregate 0.7-1.1, coarse aggregate 0-0.4, water 0.23 and water reducer 0.02-0.
03.
8. The method for preparing fiber-reinforced ultra-high performance concrete according to claim 7, characterized in that: The cement is cement with a compressive strength grade of 52.5 or above.
9. Fiber-reinforced concrete, characterized in that It comprises modified crude fibers prepared by the regenerated crude fiber modification method according to claims 1-5, wherein the surface of the modified crude fibers is coated with a graphene oxide coating, and the aspect ratio of the modified crude fibers is 30-120.
10. The fiber-reinforced concrete according to claim 9, characterized in that: By mass, the mass proportion of cement in the system is 1, and the mass proportions of the other components are: crude fiber 0.5-0.14, silica fume 0.25, limestone powder 0.25, fine aggregate 0.7-1.1, coarse aggregate 0-0.4, water 0.23 and water reducer 0.02-0.03; the cement has a compressive strength grade of 52.5 and above.
Citation Information
Cited By
Method for predicting residual compressive strength of FRP-reinforced nano-modified UHPC after high-temperature exposure
CN121054153A
Method for predicting residual compressive strength of frp reinforced nano-modified uhpc after high temperature exposure
CN121054153B
Regenerated fiber reinforced sulphoaluminate cement-based ultra-high performance concrete for retired wind turbine blade and preparation method of regenerated fiber reinforced sulphoaluminate cement-based ultra-high performance concrete
CN122277197A